Design and Development of Budget Absorption Discipline Notification Application using SDLC Method - Oktaviani, Yohana Christela; Wahyuningsih, Yulia (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2024)
Optimal budget absorption in a region requires streamlined solutions. One such solution is simplifying the budget submission process through technology-based approaches. This study utilizes the SDLC methodology to create a durable application for Public Housing, Settlement Areas, and Human Settlement Offices, meeting their requirement for an effective budget submission tool. The SDLC method allows for continuous evaluation and development according to agency requirements. The outcome is APPA, a Budget Absorption Notification Application designed for the Public Housing, Settlement Areas, and Human Settlements Office in Jember. This application has helped to ensure that the budget approval process is not a sync point in achieving project deadlines. One of the aims of this research was to develop a technology-driven solution that could be implemented to increase optimal regional absorption which is expected can facilitate and accelerate budget execution and public service delivery more prettily than ever.